2021
DOI: 10.18051/univmed.2021.v40.243-253
|View full text |Cite
|
Sign up to set email alerts
|

Viral load as a risk factor of reverse transcriptase inhibitor drug resistance mutation in antiretroviral-treated people living with HIV/AIDS

Abstract: Background The human immunodeficiency virus type 1 (HIV-1) is a major contagion faced by the population of Indonesia. The success of antiretroviral treatment (ART) is threatened by the emergence of drug resistance mutations (DRM). The aim of this study was to determine the association between CD4 count, CD4 count changes, viral load, adherence to therapy, and therapy history in the presence of DRM in people living with HIV/AIDS (PLWHA). MethodsThis was a cross-sectional study involving 269 adults who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(40 reference statements)
1
0
0
Order By: Relevance
“…Our study found that 7 out of 8 patients who had the mutations had a viral load above 1000 copies/mL. This is in line with a study by Hutapea et al (21) in Papua which also found a statistically significant relationship between the amount of HIV RNA and mutations. It was found that patients with HIV RNA values of >1000 copies/mL had a higher probability of mutations compared to patients with HIV RNA values below 1000 copies/mL.…”
Section: Discussionsupporting
confidence: 93%
“…Our study found that 7 out of 8 patients who had the mutations had a viral load above 1000 copies/mL. This is in line with a study by Hutapea et al (21) in Papua which also found a statistically significant relationship between the amount of HIV RNA and mutations. It was found that patients with HIV RNA values of >1000 copies/mL had a higher probability of mutations compared to patients with HIV RNA values below 1000 copies/mL.…”
Section: Discussionsupporting
confidence: 93%